1998
DOI: 10.1590/s0102-33061998000100008
|View full text |Cite
|
Sign up to set email alerts
|

Fungos filamentosos do solo da Ilha dos Eucaliptos na Represa do Guarapiranga em São Paulo, SP

Abstract: Iracema Helena Schoenlein-Crusius 2 RESUMO -(Fungos filamentosos do solo da Ilha dos Eucaliptos na Represa do Guarapiranga em São Paulo, SP). Foi estudada a diversidade dos fungos do solo da Ilha dos Eucaliptos na Represa do Guarapiranga em São Paulo, SP, sob floresta de Euca/yptus, mata de interseção e mata secundária remanescente, em duas épocas climaticamente distintas: março -época quente e úmida (verão) e junho -época fria c scca (inverno) de 1996. Os fungos filamentosos foram isolados pelos métodos da di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
1
5
0
2
Order By: Relevance
“…In another area of the Atlantic Rainforest, MILANEZ 1997, 1998) Backusella lampropora, Trichoderma aureoviride, T. viride and a strain of Pestalotiopsis sp., were also isolated from the soil depending on the type of plant cover, exclusively from the area having remaining secondary vegetation. In the results obtained previously by other authors a great diversity of species of Penicillium were found in contrast to Aspergillus (SANTOS et al 1998), similar to those found in this study.…”
Section: Genera Nº Speciessupporting
confidence: 93%
“…In another area of the Atlantic Rainforest, MILANEZ 1997, 1998) Backusella lampropora, Trichoderma aureoviride, T. viride and a strain of Pestalotiopsis sp., were also isolated from the soil depending on the type of plant cover, exclusively from the area having remaining secondary vegetation. In the results obtained previously by other authors a great diversity of species of Penicillium were found in contrast to Aspergillus (SANTOS et al 1998), similar to those found in this study.…”
Section: Genera Nº Speciessupporting
confidence: 93%
“…Mendes et al (2013) confirmed in their review about rhizosphere microbiome, compounds released in soil by plants may affect spore germination and fungal growth. Santos et al (1998) also reported that Eucalyptus species produce metabolites that inhibit the growth of soil fungi. Further studies are required on inhibitory effects of these metabolites on M. anisopliae to understand the interactions of these integrated systems with the soil microbiota (Rizvi et al, 1999;Sobrero, 2004;Albach et al, 2010).…”
Section: Quantification Of Infected Nymphsmentioning
confidence: 98%
“…In the State of São Paulo, the diversity of several groups of fungi is better known because surveys have been done in terrestrial and aquatic environments in some preserved or less affected Atlantic Rainforest in protected areas such as "Reserva Biológica de Paranapiacaba" (1,19,23,25,(55)(56)(57)(58)(59)69), "Parque Estadual da Ilha do Cardoso" (66,67,68,71,72) and "Estação Ecológica da Juréia-Itatins" (2,12,22,42), but also in regions relatively close (10 to 20km) to the center of the city of São Paulo, such as "Represa do Guarapiranga" (14,32,50,51,75) and "Parque Estadual das Fontes do Ipiranga", where the Botanical Institute of São Paulo is located (16,17,20,24,(36)(37)(38)(39)(40)(41)(44)(45)(46)54,70,73).…”
Section: Introductionmentioning
confidence: 99%